Subacute Invasive Pulmonary Aspergillosis Presenting With Pneumothorax - Carl W. Brasch; Allen B. Repp (Annals of Internal Medicine: Clinical Cases)
We report the case of a 43-year-old woman with subacute invasive aspergillosis after COVID-19 infection who presented with a pneumothorax. We discuss the spectrum of pulmonary disease due to Aspergillus and suggest that clinicians consider pulmonary aspergillosis in patients after respiratory viral infections such as COVID-19.